From Plato to Christ : how Platonic thought shaped the Christian faith - Markos, Louis, 1964- (InterVarsity Press, 2021)
"Christians throughout the history of the church and even today have inherited aspects of the ancient Greek philosophy of Plato. To help us understand the influence of Platonic thought on the Christian faith, Louis Markos offers careful readings of some of Plato's best-known texts and then traces the ways that his work shaped some of Christianity's most beloved theologians"--